2019
DOI: 10.1002/chem.201900655
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Improved Nerve Agent Simulants and Insights into Organophosphate Hydrolysis Reactions from DFT and QSAR Modeling

Abstract: The effective detoxification of chemical warfare agents, specifically nerve agents, is a pressing issue in the modern world. Due to the high toxicity of these molecules, simulants are often used in experiments as substitutes for the agents. However, there is little reason to believe that the current simulants used in the literature are optimal predictors of nerve agent reactivity. Density functional theory calculations were performed on the alkaline hydrolysis of over 100 organophosphate molecules to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 73 publications
(132 reference statements)
1
23
0
Order By: Relevance
“…The catalytic mechanism of acetylcholinesterase is based on the formation of a tetrahedral acyl-enzyme intermediate, and phosphate-enzyme intermediate for the chemical agent's reactions. Although extensive structural and energy calculations on the transition state of each reaction pathway would be another way of estimating the kinetic parameters, as indicated in several other reports [24,25], charge on the central phosphorus atom is used for evaluating the reactivity of the nerve agent. Therefore, charge in phosphorus atom in organophosphorus compound would be used for toxicity comparison in the limited conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic mechanism of acetylcholinesterase is based on the formation of a tetrahedral acyl-enzyme intermediate, and phosphate-enzyme intermediate for the chemical agent's reactions. Although extensive structural and energy calculations on the transition state of each reaction pathway would be another way of estimating the kinetic parameters, as indicated in several other reports [24,25], charge on the central phosphorus atom is used for evaluating the reactivity of the nerve agent. Therefore, charge in phosphorus atom in organophosphorus compound would be used for toxicity comparison in the limited conditions.…”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23][24] Recently, work undertaken by Snurr and Mendonca, has shown that density functional theory (DFT) can be used to study the mechanism of OP hydrolysis, which has resulted in the development of a quantitative structure activity relationship (QSAR) model that enables the identification of appropriate OP CWA simulants for decontamination purposes. 25 However, when considering supramolecular technologies, the moiety target is often selective coordination of the polar PvO functionality. This chemical group, common to all OP CWAs, plays a significant role in both molecular surface coordination properties and reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we extend our prior work, which showed that simple, low level computational modelling may be used to predict hydrogen bond mediated aggregation events 26,27 and antimicrobial activity, 28 to identify appropriate OP CWA simulants for the development of supramolecular detection technologies, complementing the recent advances made in this area for hydrolysis siumulants. 25 Here, we hypothesised that neutral hydrogen bond donating receptors 1-4 ( Fig. 1) would form hydrogen bonded complexes with potential OP CWA simulants and, due to the structural simplicity of 1-4, the strength of the complex formed would depend on the properties associated with the principal hydrogen bond acceptor (HBA) group.…”
Section: Introductionmentioning
confidence: 99%
“…Their production, stockpiling and use are monitored by international organizations (Organization for the Prohibition of Chemical Weapons -OPCW) [9][10][11][12][13]. Neurotoxic chemical agents have the property of irreversibly inhibiting the erythrocytary acetylcholinesterase (AChE) [14][15][16][17][18]. The coupling reaction of the organophosphoric compounds at the level of the active situs of the enzyme is represented in fig.1, 2.…”
mentioning
confidence: 99%
“…In fig. 3, the chemical structure of neurotoxic agents and their corresponding simulators are being shown [4,6,14,17,24]. The laboratory use of neurotoxic chemical agents is restricted, as they are extremely toxic substances.…”
mentioning
confidence: 99%